2023
DOI: 10.1186/s12889-023-15250-5
|View full text |Cite
|
Sign up to set email alerts
|

Can counter-advertising exposing alcohol sponsorship and harms influence sport spectators’ support for alcohol policies? An experimental study

Abstract: Background Exposure to alcohol advertising and sponsorship through elite sport is associated with harmful use of alcohol. Owing to strong financial and cultural ties between alcohol and sport in Australia, policy action to restrict alcohol sport sponsorship is unlikely to occur without strong public support for change. This study tested whether exposure to counter-advertising exposing industry marketing of harmful products—a technique shown to be effective in tobacco control—promotes higher sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…in line with previous research attesting to the effectiveness of CAs portraying alcohol harms using a negative emotional tone [ 37 ], both CAs successfully promoted knowledge of alcohol health harms and intentions to drink less. A previous study also found that the industry denormalization CA was also effective at increasing spectators’ support for policies aimed at restricting sports‐related alcohol marketing [ 49 ]. Collectively, findings suggest that CAs that direct viewers to look ‘upstream’ at systemic contributors to ‘downstream’ health problems (such as industry marketing and sport sponsorship) can help to garner public support for policy change and promote beliefs, attitudes and intentions conducive to reduced personal consumption of harmful products.…”
Section: Discussionmentioning
confidence: 99%
“…in line with previous research attesting to the effectiveness of CAs portraying alcohol harms using a negative emotional tone [ 37 ], both CAs successfully promoted knowledge of alcohol health harms and intentions to drink less. A previous study also found that the industry denormalization CA was also effective at increasing spectators’ support for policies aimed at restricting sports‐related alcohol marketing [ 49 ]. Collectively, findings suggest that CAs that direct viewers to look ‘upstream’ at systemic contributors to ‘downstream’ health problems (such as industry marketing and sport sponsorship) can help to garner public support for policy change and promote beliefs, attitudes and intentions conducive to reduced personal consumption of harmful products.…”
Section: Discussionmentioning
confidence: 99%